Phytogenic additives to decrease in vitro ruminal methanogenesis - Bodas R.; López S.; Fernández M.; García-González R.; Wallace R.J.; González J.S. (Nutritional and foraging ecology of sheep and goats, 2009)
Six plants (Carduus pycnocephalus, Populus tremula, Prunus avium, Quercus robur, Rheum nobile and Salix caprea) were tested to determine their effects as feed additives to decrease ruminal methanogenesis in vitro. The plants had been selected in a previous screening assay in which a collection of 450 plant species had been tested. Sheep fed alfalfa hay were used as donors for rumen fluid. Batch cultures were performed in 120 ml serum bottles, using 10 ml strained rumen, 40 ml medium, 500 mg DM substrate (50% alfalfa hay, 40% grass hay and 10% barley) and 50 mg DM freeze-dried ground plant additive. After 24 h of incubation, gas production, methane and volatile fatty acids (VFA) production, propionate to acetate ratio, in vitro DM digestibility, pH and fermentation efficiency were measured. All the plants tested reduced methane production (P < 0.001) in relation to the control (no plant added). P. avium and Q. robur caused a decrease in propionate production and in propionate to acetate ratio (P < 0.001), whereas S. caprea reduced propionate production (P < 0.001). Gas production, pH and fermentation efficiency were not affected by any of the plants (P > 0.05). Among them, R. nobile was particularly promising since it showed the greatest and most consistent effect on methane production (-16% in relation to the control, P < 0.001). Moreover, it enhanced ruminal fermentation, stimulating DM digestibility (P < 0.05) and VFA production (P < 0.001) and increasing propionate to acetate ratio (P < 0.001). In conclusion, among the plant species evaluated, Rheum nobile showed the most consistent effects for decreasing methane production without adversely affecting other parameters of rumen fermentation.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)